2015
DOI: 10.1073/pnas.1522643113
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, genetics, and transmissibility in ferrets of Eurasian avian-like H1N1 swine influenza viruses

Abstract: Pigs are important intermediate hosts for generating novel influenza viruses. The Eurasian avian-like H1N1 (EAH1N1) swine influenza viruses (SIVs) have circulated in pigs since 1979, and human cases associated with EAH1N1 SIVs have been reported in several countries. However, the biologic properties of EAH1N1 SIVs are largely unknown. Here, we performed extensive influenza surveillance in pigs in China and isolated 228 influenza viruses from 36,417 pigs. We found that 139 of the 228 strains from pigs in 10 pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
104
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(114 citation statements)
references
References 39 publications
8
104
1
1
Order By: Relevance
“…In contrast, 3 of the remaining 5 genotypes (that is, genotypes 4, 12, and 13) are also found in China, but they are unlikely to have been introduced into Vietnam from China. The EA-like IAV-S lineage has been constantly isolated in the Chinese pig population since 2002 (11,12), and long-term serological surveillance suggests that the EA-like IAV-S lineage had been predominant in China since 2003 (40). Nonetheless, neither EA-like IAV-S nor IAV-S containing EA-like genes have been found in Vietnam to date.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, 3 of the remaining 5 genotypes (that is, genotypes 4, 12, and 13) are also found in China, but they are unlikely to have been introduced into Vietnam from China. The EA-like IAV-S lineage has been constantly isolated in the Chinese pig population since 2002 (11,12), and long-term serological surveillance suggests that the EA-like IAV-S lineage had been predominant in China since 2003 (40). Nonetheless, neither EA-like IAV-S nor IAV-S containing EA-like genes have been found in Vietnam to date.…”
Section: Discussionmentioning
confidence: 99%
“…EA-like IAV-S and its reassortant with a human seasonal influenza virus have been endemic in Europe since the 1980s (9). Thereafter, EA-like IAV-S have spread to Thailand (10) and China (11,12).…”
mentioning
confidence: 99%
“…These viruses were previously isolated from pigs during surveillance activities conducted in China between 2009 and 2013 for swine influenza [6,7,13], and were used as challenge viruses in this study. These viruses were propagated in specific pathogen-free (SPF) embryonated chicken eggs and titrated to determine the 50% egg infective dose (EID 50 ) by the method of Reed and Muench [17].…”
Section: Virusesmentioning
confidence: 99%
“…Since 2009, an intensive surveillance program for swine influenza has been carried out in more than 20 provinces in China. This program found that EA H1N1 viruses were the predominant circulating viruses in pigs and formed two antigenic groups distinct from the classical swine H1N1 (CS H1N1) and the 2009/H1N1 viruses [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation